2020
DOI: 10.1002/asi.24443
|View full text |Cite
|
Sign up to set email alerts
|

How do multilingual users search? An investigation of query and result list language choices

Abstract: Many users of search systems are multilingual, that is, they are proficient in two or more languages. In order to better understand and support the language preferences and behaviors of such multilingual users, this paper presents a series of five large‐scale studies that specifically elicit language choices regarding search queries and result lists. Overall, the results from the studies indicate that users frequently make use of different languages (i.e., not just their primary language), especially when they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Users also are looking forward to editing or adjusting their queries to access more information. It has been confirmed that users tended to choose their native language significantly more than a second language in formulating their queries (Steichen and Lowe, 2021). They were more likely to reformulate or edit the query in the source language based on the available tools than with the machine translation (Dorr et al.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Users also are looking forward to editing or adjusting their queries to access more information. It has been confirmed that users tended to choose their native language significantly more than a second language in formulating their queries (Steichen and Lowe, 2021). They were more likely to reformulate or edit the query in the source language based on the available tools than with the machine translation (Dorr et al.…”
Section: Discussionmentioning
confidence: 91%
“…One of the biggest challenges for multilingual information retrieval lies in how to better support multilingual users from the interaction perspective. According to Steichen and Lowe (2021), multilingual user preferences are influenced by the layout of search results. Mixed-language result lists in the middle attracted the greatest attention compared with single-language result lists that affect users' behavior.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations